Developing of Measurement of Independence Characteristic in Middle School Students Mathematics and Science - Supardi U. S. Supardi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2018)
The purpose of this study to design a measurement instrument independence character of middle school students. Research using research and development (R & D). Stages of the research process include: reviewing the concept, making the construct and design the instruments, experts’ assessment, the empirical pre-test, and empirical testing. Test experts were conducted by experts through quantitative and qualitative assessments were followed by improvements to the instrument. Pre empirical testing was done by trial and instruments in small-scale followed by repair and selection of items. Empirical testing is a field test on a large scale at middle school students who were followed by the selection of grains and calculation of reliability of the instrument. Research and development results obtained as follows. (1) Measurement code developed with the student independence four dimensions: freedom, initiative, progressive and resilient, and confident. The dimension of freedom comprising: able to make their own choices and able to perform his own activities. Dimension Initiative consists of: being able to think and act in an indigenous, and doing creative activities. The results of this study are expected secondary school teachers can have a reference or guidelines for measuring the character of student independence